ChemInform Abstract: Directed Lithiation of N′‐[2‐(4‐Methoxyphenyl)ethyl]‐N, N‐dimethylurea and tert‐Butyl [2‐(4‐Methoxyphenyl)ethyl]carbamate. Issue 29 (22nd July 2014) - Smith, Keith; El‐Hiti, Gamal A.; Alshammari, Mohammed B.
Abstract Lithiation of the title substrates with BuLi followed by treatment with various electrophiles give the corresponding products having the substituent ortho to the directing group.